SPIRITUALITY AS PHILOSOPHICAL, SOCIAL AND CULTURAL DE-VELOPMENT PROBLEM - V. E. Gromov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2013)
The purpose of the article is to regard the essence and phenomenon of spirituality in connection with ontological foundation of human being existence. The author suggests the concept of new cosmo-theocentric paradigm of human world outlook, as a ground of perspective transformation of social life activity on the contrary to anthropocentric view, which dominates in present society consciousness. The author gives the characteristics of the ideal sage and underlines the importance of spiritual teachers in cultural development of society. Methodology. The method of philosophizing is connected with the unity of mind, sensuality, belief, will in integral body and mental organization of a man. Such point of view takes into consideration not only aspects of objective determination, but includes senses of existence and world outlook ideas in culture on particular and universal levels of social experience. The author considers a special ontological disposition of the human being in the world as a “transcendent project” with “metaphysic responsibility”. Scientific novelty. In the history of social culture the problem of its spiritual attitude towards reality is a basic problem, but now it becomes especially up-to-date and important. Now the survival of the civilization depends on the development of spirituality. From metaphysical point of view it means how spiritual the human being may be. The author connects the consideration of spirituality with particular human being ontological status in the world and provides his reflection with speculative character. Conclusions. The transition of modern civilized society to the cosmo-theocentric paradigm is prepared by contradictions of its technological and cultural development. In historical circumstances when the conscious influence of society on itself is growing, the realization of this process depends on spiritual trend of human beings cultural activity and mental quality of social leaders. Anthropocentrism as a world view principle is a main obstacle on the way to spiritual transformation of consumer society. This principle made the human being the cult for itself and weakened its ability for will and belief. Democratic pluralism and diversity of cultural forms, reinforcement of analytic tendency in cognition are turned into the aspects of confusion in selection the trends of social development. Many philosophers of “postmodern situation” connect democracy and pluralism with fighting against totalitarian ideologies. However, we have no person without any ideology and undoubtedly it is possible to attain consonance in the sphere of main morality values.